2019
DOI: 10.1177/2325967119857592
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Medial Ulnar Collateral Ligament of the Elbow: Biomechanical Comparison of a Novel Anatomic Technique to the Docking Technique

Abstract: Background:In recent years, understanding of the anatomy of the ulnar collateral ligament (UCL) has evolved, demonstrating that the insertional footprint of the UCL on the ulna is more elongated and distally tapered than previously described. Current UCL reconstruction configurations do not typically re-create this native anatomy, which may represent a potential area for improvement.Purpose/Hypothesis:The purposes of this study were (1) to describe a novel anatomic UCL reconstruction technique designed to bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
1
22
0
5
Order By: Relevance
“…There are a multitude of techniques described for primary UCL reconstruction including the original figure of 8 technique by Jobe in 1986 [1], the docking technique [6,30], the modified Jobe [18], the DANE TJ technique [7], interference screw only [31], and a newly described anatomic reconstruction [32]. A survey of MLB orthopedic surgeons revealed a preference for the docking technique with palmaris autograft [33].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…There are a multitude of techniques described for primary UCL reconstruction including the original figure of 8 technique by Jobe in 1986 [1], the docking technique [6,30], the modified Jobe [18], the DANE TJ technique [7], interference screw only [31], and a newly described anatomic reconstruction [32]. A survey of MLB orthopedic surgeons revealed a preference for the docking technique with palmaris autograft [33].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…6,15,19,20,24,29 First described by Frank Jobe in 1986, the procedure has undergone significant evolution in terms of refinement of technique, surgical approaches, variations in tunnel drilling, graft choice, and fixation methods. 1,7,8,18,21 Return to play at the same or higher level has also been reported at rates between 83% and 95%. 6,10,11,23,28 In contrast, repair, rather than reconstruction, of the UCL had historically poorer return-to-sport outcomes, ranging between 29% and 63%.…”
mentioning
confidence: 96%
“…The purpose of this study was to compare the gap size under valgus stress of the ''anatomic'' UCLR technique 3 versus the standard docking technique. We hypothesized that the anatomic technique, which restores the native UCL insertion using more distal fixation, would provide greater resistance to valgus stress (smaller increase in ulnohumeral gap) as compared with the standard docking technique.…”
mentioning
confidence: 99%
“…Rather than a simple attachment on the sublime tubercle, the ligament insertion tapers as it extends distally along a consistent osseous ridge, with a mean length of 27.4 to 29.2 mm, 9,19 a mean width of 4.0 to 7.6 mm, 1,17 and an average insertional area of 187.6 mm. 3,4,9 As a result, surgeons have considered moving their reconstruction position more distally. Although the distal UCL fibers do not significantly contribute to gap resistance, 6 Camp et al 3 showed that a reconstruction with a larger distal ulnar attachment fails at higher loads than a reconstruction with the more traditional proximal ulnar attachment.…”
mentioning
confidence: 99%